Can Energy Efficiency Help in Achieving Carbon-Neutrality Pledges? A Developing Country Perspective Using Dynamic ARDL Simulations - Hossain, Md Emran; Rej, Soumen; Saha, Sourav Mohan; Onwe, Joshua Chukwuma; Nwulu, Nnamdi; Bekun, Festus Victor; Taha, Amjad (Mdpi, 2022)
The current research sheds light on the nexus between environmental degradation as proxied by carbon dioxide emissions (CO2), energy efficiency (EE), economic growth, manufacturing value-added (MVA), and the interaction effect of EE and MVA in India. Using yearly data from 1980 to 2019, the current study employs dynamic auto-regressive distribution lag (DARDL) simulations and Fourier Toda and Yamamoto causality techniques. The findings of DARDL reveal that as income and MVA rise, environmental quality decreases, while EE improves environmental conditions in both the long and short run. Surprisingly, the interaction term of EE and MVA has a detrimental influence on environmental quality, meaning that India remains unable to provide energy savings technologies to the manufacturing industry. Furthermore, the environmental Kuznets curve (EKC) hypothesis is well-founded for India, as the long-run income coefficient is smaller than the short-run coefficient, implying that India is in its scale stage of economy, where economic growth is prioritized over environmental quality. The results of the causality technique reveal that CO2 emissions and EE have a bidirectional association. Therefore, policymakers in India should embrace realistic industrialization strategies combined with moderate decarbonization and energy efficiency initiatives under the umbrella of sustainable industrial and economic growth.
Keywords: energy efficiency; dynamic ARDL; industrialization; INDCs; Make in India; carbon neutrality